Welfare State Chauvinists? Gender, Citizenship, and Anti-democratic Politics in the Welfare State Paradise - Finnsdottir, Maria; Hallgrimsdottir, Helga Kristin (Frontiers in Sociology, 2019)
The rise of the far-right poses a pressing challenge to democratic politics and the democratization of political participation in Western Europe. This paper addresses this issue in the Scandinavian context, examining the importance of welfare chauvinism and gendered citizenship claims in the political rhetoric of the far-right. In so doing, we contribute to a need to examine closely the interplay between gender, citizenship, and welfare politics and the rise of exclusionary and anti-democratic politics. The paper draws on an examination of the party platforms of the three principle far-right-wing parties currently active in Scandinavia: the Danish People’s Party, the Norwegian Progress Party, and the Sweden Democrats as well as descriptive statistics on ethnonationalist tendencies among the Scandinavian populations in recent years, retrieved from the International Social Survey Programme’s (ISSP) 2013 survey on nationalism. We conclude that the far-right in Scandinavia uses gender and ethno-nationalist claims to simultaneously valorize and challenge egalitarianism in the welfare state while also shoring up exclusionary and anti-democratic claims to citizenship and belonging in the Nordic welfare state.